Let's Talk about Bias in Healthcare: Experiences from an Interactive Interprofessional Student Seminar - Mckenzie P. Rowe; Nancy B. Tahmo; Opeoluwa O. Oyewole; Keyonna M. King; Teresa M. Cochran; Yun Saksena; Carolyn T. Williamson; Rev. Portia A. Cavitt; Sherrita A. Strong; Michael D. Griffin; Timothy C. Guetterman; Jasmine R. Marcelin (University Library System, University of Pittsburgh, 2024)
Background: Education to increase awareness of the impact of bias in healthcare should be included in all health professions training programs. This report describes the implementation and outcomes of an interactive, interprofessional pilot seminar on racial bias in healthcare for health professions students. Methods: Forty students across the University of Nebraska Medical Center's six health profession colleges participated in a 3-part, 1-hour seminar, including a video vignette depicting examples of bias in the hospital, facilitated interprofessional small group discussions, and interaction with a health equity expert panel. We analyzed the results of participants' Ethnic Perspective-Taking (EP) and Implicit Bias Knowledge scale (IBKS) scores before and after the seminar. Results: There was a statistically significant increase (p<0.001) in the average post-seminar EP scores (30.6 post-seminar vs 27.8 pre-seminar). For the adapted IBKS, there were significant improvements in participant knowledge, skills to identify, and ability to explain the impact of implicit biases (p<0.05). Participants highlighted the importance of including education about bias in healthcare training, and some suggested mandatory education. All facilitators agreed that learners gained a deeper appreciation for the effect of bias and racism on health outcomes and participants understood how bias and racism affect patient care and clinician experience after the seminar. Conclusion: Health professions training often lacks integrated interprofessional and health equity education. This seminar addresses both, engaging community voices without heavy resources. Despite low participation, results show the benefits of interactive sessions on health equity, helping students grasp their role in equitable care and influencing future practice.